Biological inorganic chemistry : a new introduction to molecular structure and function - Crichton, Robert R. (Academic Press, an imprint of Elsevier, 2019)
"Beginning with an overview of metals and selected nonmetals in biology, the book supports the interdisciplinary nature of this vibrant area of research by providing an introduction to basic coordination chemistry for biologists and structural and molecular biology for chemists. Having built this accessible foundation, the book progresses to discuss biological ligands for metal ions; intermediary metabolism and bioenergetics; and methods to study metals in biological systems. This valuable resource also covers metal assimilation pathways; transport, storage, and homeostasis of metal ions; the biological chemistry of iron; and copper chemistry and biochemistry. In addition, the book discusses non-metals in biology; metals in the brain; metals and neurodegeneration; metals in medicine and metals as drugs; and metals in the environment, and much more." --back cover
Includes index.
Keywords: Bioinorganic chemistry.; elektronické knihy; electronic books